2022
DOI: 10.1103/physrevd.106.056020
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic pressure of magnetized quark matter with anomalous magnetic moment

Abstract: We investigate magnetic field ( ) dependence of constituent quark mass, the longitudinal and transverse pressure as well as the magnetization and magnetic susceptibility of strongly interacting quark matter. We employ the two-flavour Polyakov Nambu-Jona-Lasinio model with the inclusion of the anomalous magnetic moment (AMM) of the quarks at finite temperature ( ) and finite quark chemical potential ( ) capturing different stages of chiral phase transition. We find that the transverse pressure, magnetization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 132 publications
(164 reference statements)
1
2
0
Order By: Relevance
“…Although the change seems insignificant, it is concluded that the AMM enhances the splitting of the pressures parallel and transverse to the magnetic field direction. The anisotropy of the quark matter is consistent with the results reported in [37,51]. However, in panel (c), the two AMM cases are nearly indistinguishable in the chiral restoration due to our ansatz that the AMM is proportional to the square of the quark condensate.…”
Section: Numerical Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the change seems insignificant, it is concluded that the AMM enhances the splitting of the pressures parallel and transverse to the magnetic field direction. The anisotropy of the quark matter is consistent with the results reported in [37,51]. However, in panel (c), the two AMM cases are nearly indistinguishable in the chiral restoration due to our ansatz that the AMM is proportional to the square of the quark condensate.…”
Section: Numerical Results and Discussionsupporting
confidence: 88%
“…This scheme separates the potential divergences in pure vacuum from the finite magnetic contributions. The VMR scheme is not only able to eliminate the unphysical oscillatory behavior in chiral quark condensate or tachyonic neutral pion masses that are observed when using the non-magnetic-field independent regularization (non-MFIR) scheme [51], but can also achieve the paramagnetism of QCD matter [52]. In our present work, we employ the VMR scheme to regularize the thermodynamic potential divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many works have been dedicated to the effects of magnetic fields on the quantum chromodynamics (QCD) phase transition [1,2] and the equation of state in quark (neutron) stars [3][4][5][6][7][8]. The magnetic field modifies the microscopic properties of quark matter with the corresponding macroscopic implication in compact stars [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%